The Effect of Income Inequality, Average Schooling Duration, and Social Assistance on Poverty in Gerbangkertosusila - Prabowo, Riki Adi; Hutabarat, Ruth Eviana (Journal of Tourism Economics and Policy, 2026)
This study aims to analyze the effect of income inequality, average length of schooling, and social assistance on poverty levels in the Gerbangkertosusila region during the period 2020–2024. This study uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS). The analysis method used is panel data regression with a Fixed Effect Model (FEM) selected through the Chow Test and Hausman Test. The results show that average length of schooling has a significant and negative effect on poverty, indicating that increased access to and achievement in education can reduce the economic vulnerability of communities. In addition, social assistance has been shown to have a significant impact on reducing poverty, underscoring the importance of social protection programs as a means of improving the welfare of poor households. Conversely, income inequality does not have a significant effect on poverty, meaning that income inequality is not yet a dominant factor in changes to poverty levels in the region. These findings emphasize that strengthening the quality of education and optimizing the distribution of social assistance are key strategies for accelerating poverty reduction efforts in the Gerbangkertosusila region.